A cross-linguistic comparison of reference across different signed languages - Leeson, Lorraine (My University, 2020)
Do deaf signers of different signed languages do reference the same way? Here we compare how signers of five signed languages coordinate fully conventionalised forms (such as lexical manual signs, fingerspelling and/or spoken language mouthings) with more richly improvised semiotics (such as indicating verbs, pointing signs, depicting signs, visible surrogates and/or invisible surrogates) to identify and talk about referents of varying agency. The five languages are Auslan, Norwegian Sign Language, Finnish Sign Language, Swedish Sign Language and Irish Sign Language.
High Desert Linguistics Conference (HDLS14)
Keywords: Digital Humanities; Auslan; Finnish Sign Language; Irish Sign Language; Norwegian Sign Language; Semiotics; Swedish Sign Language; Communication; Deaf/Deafness